Guidelines, recommendations and tool for non-formal learning method - Hassinen, Sirje (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
Rapid changes in society and technology require adaptation both in working life and education. Lifelong, continuous learning, unlearning, and relearning are more important now than ever before. Different European policy documents and processes highlight establishing a new lifelong learning culture. These focus on more flexible and permeable vocational education and training systems, the validation of non-formal and informal learning. CEDEFOP defines lifelong learning as all learning activity undertaken throughout life, with the aim of improving knowledge, skills/competences and/or qualifications for personal, social and/or professional reasons. Learning can be imparted anywhere and everywhere, acquired in a formal, non-formal or informal setting.